Medülla spinalis travmalarının değerlendirilmesi - (:unkn) unknown (My University, 2004)
Medülla spinalis yaralanmaları, vertebral kolonun veya vertebral kanalın travmasına bağlı oluşmaktadır. Medulla spinalis hasarından, adale kuvvetinde azalma ve his kusurunu içeren sinir sisteminin tüm fonksiyonlarında etkilenme meydana gelebilmektedir. Adli tıp pratiğinde medülla spinalis travmalarında; hayati tehlike, mutad iştigal, uzuv zaafi-tatili, ve maluliyet sorularıyla karşılaşılır. Bu gibi olgularda; mahkemelerce Adli Tıp Kurumu 3. İhtisas Kurulundan son görüş istenmektedir. Bu çalışmada, 3. İhtisas Kuruluna 1997-2000 yılları arasında gönderilen olgular; yaş, cinsiyet, travma türü, klinik bulgular, yaralanan vertebra bölgesi, hayati tehlike, mutad iştigal, uzuv zaafi-tatili yönünden değerlendirilmiştir. 4 yıllık sürede 464 olgu muayene edilmiştir. Bu olguların 328'i (%70,7) erkek, 136'sı (%29,3) kadın olup yaş ortalaması 36,4'dür. Travma türü açısından %68,2 ile en çok rastlanan trafik kazasıydı. Yaralanan vertebra bölgesine göre; lumbal bölge %41,7, torakal bölge %39,7, servikal bölge %18,6 ile sıralandı. Elde edilen bulgular, yapılan diğer çalışmaların verileriyle karşılaştırıldı.

The injury of medulla spinalis can be related with the trauma of vertebral colon or vertebral channel. The damage of medulla spinalis can effect all the functions of nervous system including insufficient muscle power and sense defect. In the practice of forensic medicine, the injuries of medulla spinalis which occurred as a result of trauma appear with the questions of life-threat, delay of daily life, organ insufficiency or organ failure and disability. The last official report in these kind cases is prepared by the 3rd Specialization Board of Institute of Forensic Medicine. In this study, the cases that were evaluated by the 3rd Specialization Board are classified according to their age, sex, trauma type, clinical findings, injured vertebral zone, life-threat, delay of daily life, and organ insufficiency or organ failure. During the period of four years, the reported 464 cases were examined. 328 cases of all (70,7 %) were men, 136 cases (29,3 %) were women, and the mean age was 36,4 (between 6 and 73 years of age). According to the type of trauma, most seen type was traffic accident in 68,2 % (303 cases). According to the injured/wounded vertebral zone, it was determined that in 191 cases (41,7 % of the cases) lumbal vertebra, in 182 cases (39,7 % of the cases) thoracal vertebra, in 63 cases (18,6 % of the cases) cervical vertebra was injured. We compared our results with the other studies.
The evaluation of spinal cord trauma
Keywords: Adli Tıp